Risk management following international standards in the routine of an umbilical cord blood bank (Research, Society and Development, 2022)
This work demonstrates the main elements of the risk management system at a Brazilian umbilical cord blood bank, taking into account the criticality and individuality of the procedures as well as regulatory and certifying agency guidelines. This study involved the implementation of a Risk Management Committee which was responsible for process flow mapping; identifying, analyzing, classifying, treating, and monitoring risks using brainstorming, flowcharts, Pareto distribution, Ishikawa diagrams, and FMEA. Almost 900 risks were divided into 16 sectors, with 24% of total risks in the Blood Processing sector, demonstrating a strong relationship between critical activities and exposure to risks. Occurrence and severity were defined, followed by risk treatment and monitoring. The risk management system provided a more reliable infrastructure to customers and employees, upgraded the capabilities of the company, successful ISO 9001: 2015 certification, and renew American Association of Blood Bank accreditation. This paper presents a specific look at the implementation of a risk management system in a private umbilical cord blood bank. Typically, this sort of information is kept in internal company documents and is not widely disclosed in the literature. In this sense, this study presents a useful perspective for practitioners and academics.